DIPLOMATIC RELATIONS BETWEEN THE REPUBLIC OF KAZAKHSTAN AND KINGDOM OF SPAIN (International relations and international law Journal, 2016)
In this article relations between Kazakhstan and Spain in the spheres of diplomacy, economic, trade, culture and tourism are researched
Keywords: diplomatic relations; foreign policy